Evidence for metastable behavior of Ga-doped CdTe - Płaczek-Popko, Ewa; Gumienny, Zbigniew; Trzmiel, Justyna; Szatkowski, Jan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
In this paper, we report for the first time on persistent photoeffects in gallium doped CdTe. Persistent photoconductivity and photoinduced persistent absorption were observed at 77 K. Both effects quenched above 120 K. The photoeffects have been attributed to the metastable behavior of gallium in CdTe.
Optica Applicata, Vol. 38, 2008, nr 3, s. 559-565
Keywords: optyka; semiconductors; semiconducting compounds; CdTe; DX centers; persistent photoeffects